Имена русских побед. 100 великих полководцев - Семенов К. К. (Вече, 2014)
Экземпляры: Ф-21 (20160120) / Инвентарный номер: 49489 / Цена: 200.00 / Сис.шифр: 63.3(2) / Авт.знак: И 51 / ГРНТИ: 03.23 / ББК: 63.3(2)